(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: Personality traits are related to cigarette smoking. However, little is known about the link between smoking and change in personality. Therefore, the present study examined whether current cigarette smoking is associated with personality change among nurses. Methodology: This cross-sectional study was conducted on 200 nurses working at Baquba Teaching Hospital and Baladrooz general hospital in Diyala Governorate, from September15, 2023 to January10, 2024. A non-probability purposive sample technique was utilizing in current study, the personality traits assessment toward smoking were assessed using the personality assessment questionnaire (PAQ). The data were analysed using Statistical Package for Social Science (SPSS) version 26. Descriptive statistics were used in this study (e.g., mean, standard deviation, frequency, and percentage). For quantitative data Pearson correlation, and the Chisquare test was employed to determine the degree and direction of the relationship between the smoking cigarrete and personality traits among nursing. Results: There were 200 participants whose mean age (± SD) of 28.97 (±6.695) years old. Moreover, 69.5% of the participants were aged 20 to 29 years old. 95 %